A Review: Integrating Content-Based and Task-Based Approach for Teaching and Learning - Safriyaldi Rahadi Hasibuan (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
Giving Indonesian learners the tools they need to communicate effectively in English is the main goal of English language instruction there. But research has shown that the communicative English skills of Indonesian school graduates remain low. In order to improve students’ communicative abilities in Indonesia more quickly, this conceptual review paper seeks to highlight the viability of the CBLT and TBLT approach. In this literature study method, researchers looking for data or information related to the potential benefits, enhance the function, efficacy, and significance of CBLT and TBLT in language learning environments by refining language teaching methodologies and the processes involved in learning a second language. The results of this research provide the information from some previous study of CBLT and TBLT in improving students’ English Skill. The conclusion from this research is that the learning process have a positive perception of the use of CBLT and TBLT approach in learning English. It has many benefits to support students’ learning process because CBLT and TBLT approach encourages intrinsic motivation in students, encourages natural learning, and helps them build language skills that can help them become more proficient communicators more quickly.